A SEMI BLIND DWT-SVD VIDEO WATERMARKING - Jyoti Bala and Dr. Shweta Rai (International journal of economic perspectives, 2022)
Digital watermarking was introduced due to rapid advancement of networked multimedia systems. It was developed to enforce copyright technologies for protection of copyright ownership. This technology is first used for still images but recently they have been developed for other multimedia objects such as audio, video etc. In this paper a new digital video watermarking scheme is proposed which combines Discrete wavelet transform (DWT) and Singular Value Decomposition (SVD) in which watermarking is done in the high frequency sub band and then various attacks have been applied. Tests have been undergone to check the proposed scheme for robustness and imperceptibility.